238Pu elimination profiles after delayed treatment with 3, 4, 3LI(1, 2HOPO) in female and male Swiss-Webster mice. (November 2014) - An, Dahlia D.; Villalobos, Jonathan A.; Morales-Rivera, Joel A.; Rosen, Chris J.; Bjornstad, Kathleen A.; Gauny, Stacey S.; Choi, Taylor A.; Sturzbecher-Hoehne, Manuel; Abergel, Rebecca J.
Abstract Purpose: To characterize the dose-dependent and sex-related efficacy of the hydroxypyridinonate decorporation agent 3, 4, 3-LI(1, 2-HOPO) at enhancing plutonium elimination when post-exposure treatment is delayed. Materials and methods: Six parenteral dose levels of 3, 4, 3-LI(1, 2-HOPO) from 1–300 μmol/kg were evaluated for decorporating plutonium in female and male Swiss-Webster mice administered a soluble citrate complex of 238Pu and treated 24 hours later. Necropsies were scheduled at four time-points (2, 4, 8, and 15 days post-contamination) for the female groups and at three time-points (2, 4, and 8 days post-contamination) for the male groups. Results: Elimination enhancement was dose-dependent in the 1–100 μmol/kg dose range at all necropsy time-points, with some significant reductions in full body and tissue content for both female and male animals. The highest dose level resulted in slight toxicity, with a short recovery period, which delayed excretion of the radionuclide. Conclusions: While differences were noted between the female and male cohorts in efficacy range and recovery times, all groups displayed sustained dose-dependent 238Pu elimination enhancement after delayed parenteral treatment with 3, 4, 3-LI(1, 2-HOPO), the actinide decorporation agent under development.